A Study on Improvement of Electronic Library Services Using User Review Data in Mobile App Market - Noh, Younghee; Ro, Ji Yoon (International Journal of Knowledge Content Development & Technology, 2021)
This study aims to analyze users’ assessment of electronic libraries in the mobile app market and promote service improvement based on this. To this end, the basic background and purpose of the research, research method, and research scope were first set, and the relevant literature and empirical prior studies were analyzed. Next, users’ evaluations of electronic libraries were collected and analyzed from Google Play Store. Based on the results analyzed, measures to improve the quality of electronic libraries were discussed. Based on the results of the study, the following improvement measures are proposed: 1) Need for systemic improvement and stabilization; 2) Provision of applications suitable for multi-device environments; 3) Resumption of services after systematic inspection after updating; 4) Simplification of sign up, log in, and authentication procedures; 5) User support through real-time chat; 6) Introduction of a detailed assessment of reviews; 7) Provision of guidance and user manual for electronic libraries; 8) Improvements to expand user convenience; and 9) Securing differentiation from other similar services. URL: http://ijkcdt.net/xml/28379/28379.pdf